214 Impact of Cochlear Dose on Hearing Preservation Following Stereotactic Radiosurgery in Treatment of Vestibular Schwannomas: A Multi-Center Study. (April 2023) - Klein, Andrea Lauren; Chang, Steven D.; Muacevic, Alexander; Sherman, Jonathan H.; Romanelli, Pantaleo; Maria, Peter Santa; Fuerweger, Christoph; Zanetti, Isa Bossi; Beltramo, Giancarlo; Vaisbuch, Yona; Tran, Emma; Feng, Austin Y.; et al.
Abstract : INTRODUCTION: Stereotactic radiosurgery (SRS) is a well-established treatment option for patients with vestibular schwannomas (VS). Hearing loss remains one of the main morbidities of VS and its treatments, including SRS. Effects of radiation parameters of SRS on hearing remains largely unknown. METHODS: Multicenter retrospective analysis of 611 patients who underwent SRS for VS from 1990 to 2020 and had pre- and post-treatment audiograms. RESULTS: Pure tone averages (PTA)s increased and word recognition scores (WRS)s decreased in the treated ears at 12 - 60 months while it remained stable in the untreated ears. Higher baseline PTA, higher tumor radiation dose, higher maximum cochlear dose, and usage of single fraction resulted in higher post radiation PTA; WRS was only predicted by baseline WRS and age. Of these parameters, higher baseline PTA, single fraction treatment, higher tumor radiation dose, and higher maximum cochlear dose resulted in a faster deterioration in PTA. Below a maximum cochlear dose of 3 Gy, there were no statistically significant changes in PTA or WRS. CONCLUSIONS: Decline of hearing at 1 year in VS patients after SRS is directly related to maximum cochlear dose, single versus 3-fraction treatment, total tumor radiation dose, and baseline hearing level. The maximum safe cochlear dose for hearing preservation at 1 year is 3 Gy, and the use of 3 fractions instead of 1 fraction was better at preserving hearing.